Effect of Fuel Type on Flow-Thermal Field Evolution and Preheating Performance of Scrap in Molten Iron Ladle - Ming Fu, Yi; Giang Liu, Guang; Yue Xu, Lan (Archives of Foundry Engineering, 2026)
Against global carbon neutrality targets, the carbon-intensive steel industry bears severe decarbonization stress, wherein advanced low-carbon smelting technologies dominate its green transition. Scrap preheating boosts scrap ratio and cuts steelmaking carbon emissions; optimized fuel-scrap matching and fuel grading by scrap type significantly improve thermal efficiency and reduce preheating energy demand. This work establishes a 3D numerical model for randomly stacked scrap within a 100-t hot metal ladle to compare natural gas, coke oven gas and converter gas regarding flow field, flame structure, thermal distribution, scrap heating performance and energy efficiency under equal total heat input. Numerical simulations with the k-ε turbulence, EDC combustion and P-1 radiation models are performed to couple flow, heat transfer and combustion. Fuel composition strongly governs flame morphology and thermal behaviors. Natural gas and converter gas form intact, stiff flames, while coke oven gas produces discontinuous unstable flames. Flow intensity decreases in the sequence converter gas, coke oven gas and natural gas, and high-speed turbulent fluctuation of converter gas facilitates heat diffusion. Under the same heating duration, the average surface temperatures of scrap are 695 K, 782 K and 411 K for natural gas, converter gas and coke oven gas, respectively. Converter gas achieves the highest preheating efficiency of 11.2 %, followed by natural gas (5.9 %), and coke oven gas is the lowest (2.4 %) due to its low calorific value. Moreover, fuel-scrap matching characteristics reveal that natural gas is suitable for light and thin scrap to avoid overheating, while converter gas is more favorable for medium and heavy scrap with improved heat penetration. This work reveals the influence mechanism of gas type on ladle scrap preheating and provides theoretical support for fuel selection and process optimization in high-efficiency and low-carbon scrap preheating applications.